A moderating role of board characteristics on the effect of antecedents on the stage of enterprise risk management implementation - Dabari, Ishaya John (2016)
Enterprise Risk Management (ERM) has become an important issue of increasing attention among the business community throughout the world. However, the concept is still relatively new among Nigerian companies and little is known about why many organizations are not fully implementing it. The main objective of this study is to examine the current state of ERM practices and the stage of its implementation in the Nigerian banking sector. The study further examined the effect of the antecedents on the stage of ERM implementation, and evaluated the moderating effect of board characteristics on the relationship between antecedents and the stage of ERM implementation. The study used a survey approach to collect cross-sectional data across 361branches and the headquarters of the 21 Nigerian commercial banks using 722 respondents. The response rate is 60 percent. Logistic Regression Model was used for data analysis. The finding revealed that there is an ERM complete in place in majority of the banks. Furthermore, the finding showed that internal audit effectiveness, human resource competency and top management commitment effect significant influence on the stage of ERM implementation while regulatory influence had partial effect. Likewise, there is a moderating effect of board characteristics on internal audit effectiveness and the stage of ERM implementation. The finding has a policy implication for the Board of Directors to improve their oversight functions and the regulatory authorities to entrench risk based supervision in all the Nigerian banks. Nevertheless, the study has limitation in terms of power of prediction with respect to measurement scale of the dependent variable and the respondents. Future research is therefore needed to evaluate the effectiveness of ERM process using a more robust scale and top management as respondents. Therefore, a clarion call is made to introduce an ERM practices across all the Nigerian companies irrespective of their status.